2022
DOI: 10.3390/antibiotics11121816
|View full text |Cite
|
Sign up to set email alerts
|

Studies Regarding the Antimicrobial Behavior of Clotrimazole and Limonene

Abstract: The paper presents the results of the studies performed to establish the effect of the mixtures between limonene and clotrimazole against microbial pathogens involved in dermatological diseases, such as Candida albicans, Staphyloccocus aureus, and Escherichia coli. Preliminary data obtained from the studies performed in microplates revealed a possible synergism between the mixture of clotrimazole and limonene for Staphylococcus aureus. Studies performed “in silico” with programs such as CLC Drug Discovery Work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The docking simulations were performed by CLC Drug Discovery Workbench Software (QIA-GEN, Aarhus, Denmark) and MVD Molegro Virtual Docker Software (QIAGEN, Aarhus, Denmark). The exact validation protocols were described in the authors' previous studies [22,23].…”
Section: In Silico Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The docking simulations were performed by CLC Drug Discovery Workbench Software (QIA-GEN, Aarhus, Denmark) and MVD Molegro Virtual Docker Software (QIAGEN, Aarhus, Denmark). The exact validation protocols were described in the authors' previous studies [22,23].…”
Section: In Silico Studiesmentioning
confidence: 99%
“…Molecular docking simulations were performed using CLC Drug Discovery Workbench Software, v. MVD 2019.7.0 (QIAGEN, Aarhus, Denmark), and MVD Molegro Virtual Docker Software, v. 1.5.1. (QIAGEN, Aarhus, Denmark) protocols, as previously described [22,23].…”
Section: In Silico Assaymentioning
confidence: 99%
“…The Supplementary Material, Tables S1 and S2 show the complete data on the intermolecular interactions between the curcumin docked with 5ZTN in comparison with the 20 test vegetal compounds, by CLC Drug Discovery Workbench Software (QIAGEN Aarhus, Denmark) and by MVD Molegro Virtual Docker Software (Molexus IVS, Rørth, Denmark), using protocols previously established and validated [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In silico, molecular docking study was conducted to predict the probable binding site and mode of binding of the 21 test vegetal compounds with dual-specificity tyrosine-regulated kinase 2, DYRK2, (PDB ID: 5ZTN) [ 30 ]. The docking studies have been performed using CLC Drug Discovery Workbench Software (QIAGEN, Aarhus, Denmark) and MVD Molegro Virtual Docker Software (Molexus IVS, Rørth, Denmark) protocols, as previously described [ 31 , 32 ]. As a general concept, molecular docking allows an accurate prediction of the optimized conformation of tested compounds (as ligands) and their target receptor protein to achieve a stable complex.…”
Section: Methodsmentioning
confidence: 99%
“…Wah Wah Aung and his colleagues developed bioactive de-chlorophyll rhein-rich Senna alata extracts for improvements in cosmeceuticals and pharmaceuticals, and they demonstrated that a rhein-rich extract and its de-chlorophyll extracts possess antioxidant, anti-inflammatory, and antibacterial activities [3]. The results obtained by Schroder Verginica and her collaborators indicated a synergism between the mixture of clotrimazole and different citrus essential oils against Staphylococcus aureus, methicillin-resistant Staphylococcus aureus (MRSA), and Pseudomonas aeruginosa, microbial pathogens that are usually responsible for skin infections [4].…”
mentioning
confidence: 99%